Peran Pengalaman Kerja Karyawan pada UMKM Millecreps Sinok Karawang - Hari Sandi, Santi Pertiwi; Asyifa, Asyifa; Gunawan, Dinar Mustika; Hidayaty, Dwi Epty (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Superior human resources are needed in businesses and companies to achieve goals in organizations or activities. The purpose of this observation is to determine the role of work experience in order to create quality employee performance. The methods used are the results of interviews, observations and literature reviews. For the sake of goals and efforts to be achieved, MSME actors need experienced human resources. Millecrepes Sinok Karawang is an MSME that sells food, this business actor needs employees who are good at cooking. If an employee has less experience in their field, the quality of work will be low and will have an impact on the progress of his business so that the business is not productive. The result of this observation if employees have work experience in their fields, it will create good quality employee performance, knowledge, skills or mastery of work, and a sense of responsibility so that business does not stop because employees have previous experience so as to create good performance quality and products produced accordingly. Keywords: Work Experience, Quality of Employee Performance